The IMPLEMENTATION OF WASTE DIAPERS AS CROP PLANT MEDIA BASED ON DIGITAL ECO- LITERATURE - ahmad iklil saifulloh; Engkin Suwandana; Akhmad Fatoni (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2021)
The aims of this program were PKK and Karang Taruna Karya Pemuda Sumbertani who were domiciled in the village of Mojorejo. Mojorejo villagers were lazy in separating waste, processing organic matter into compost, and reselling inorganic waste to the local unit waste bank. Because it is difficult to process and reuse is organic waste and diapers. Both type of those waste cannot be burned because of the water content was high. So to solve the problems some citizens throw the diapers into the river. To solve partner’s problems are to carry out the processing of waste diapers into the planting medium. The purpose of this activity is to resolve the problem of waste that categorize as the most or highest level of pollution that contaminating the environment than other types of waste. Partners also get benefits in social and health care, the economy increased due to drought did not have a negative impact on agriculture, and also the environment becomes cleaner and reduced the pollution of the environment, and also as the absorption of water in the dry season. The method is spareted into two stages; 1) increasing public awareness through counseling on the impact of diapers waste; 2) the use of diapers as a planting medium. The results obtained were the community was much more aware of not throwing garbage and diapers on the riverbanks and secondly, during the pandemic, people felt it was helped to cultivate the land around the house to meet their daily needs.